The space vector analysis of a squirrel-cage induction motor allowing for all MMF and permeance harmonics - Van der Merwe, Carel (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Ing.) -- University of Stellenbosch, 1993.